2022
DOI: 10.3390/ijerph19169938
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Risk Characteristics of Traffic Accidents in Small-Spacing Expressway Interchange

Abstract: Many small-spacing interchanges (SSI) appear when the density of the expressway interchanges increases. However, the characteristics of traffic accidents in SSI have not been explained clearly. Therefore, this paper systematically takes the G3001 expressway in Xi’an as the research object to explore the accident characteristics of SSI. Firstly, the expressway is divided into four sections. Furthermore, their safety can be evaluated by the number of accidents per unit distance of 100 million vehicles (NAP). Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This was achieved by implementing a policy that permitted only vehicles on the outer and auxiliary lanes to change lanes inward near the exits [21,42]. Wang developed a regression model to explore the accident characteristics of small-spacing interchanges based on the number of accidents counted [43].…”
Section: Small Spacing Interchange Improvement Methodsmentioning
confidence: 99%
“…This was achieved by implementing a policy that permitted only vehicles on the outer and auxiliary lanes to change lanes inward near the exits [21,42]. Wang developed a regression model to explore the accident characteristics of small-spacing interchanges based on the number of accidents counted [43].…”
Section: Small Spacing Interchange Improvement Methodsmentioning
confidence: 99%
“…Several studies have pointed out various factors that cause traffic accidents and fatalities (e.g., [19]). This research has identified the following factors (apart from driver uncertainty) that contribute to accidents, as follows: environmental conditions, the state of infrastructure, and technical vehicle causes [20]. Moreover, fatigue [21], alcohol [22], emotional state, drowsiness, headaches [23], respiratory illnesses, and fever [24,25] are conditions that increase the likelihood of a traffic accident.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The prevalence of driving under the influence poses significant risks, with drunk driving incidents accounting for a large fraction of road accidents [1] [2].With persistent high fatalities from traffic accidents, the focus on driving safety is more critical than ever. Research highlights that driver distraction, fatigue, intoxication, and environmental misjudgment are among the leading causes of vehicular accidents, underscoring the need for real-time monitoring systems that ensure driver and environmental safety [3]. The advent of artificial intelligence, machine vision, and sensor technology heralds new solutions to these challenges.…”
Section: Introductionmentioning
confidence: 99%